The effect of terrorism on economic inequality in democracies and non-democracies - Daniel Meierrieks (European Journal of Political Economy, 2025)
We examine the relationship between terrorism and economic inequality for 163 countries between 1980 and 2018. We provide robust evidence that more terrorist activity results in higher levels of income inequality, where this relationship is especially pronounced for democratic countries. As an extension, we also study the role of terrorism in wealth inequality, uncovering similar linkages. Our findings imply that democracies see lower levels of income inequality in the absence of terrorism but increases in inequality as terrorist activity grows, while inequality in non-democratic countries is not affected by terrorism. Exploring potential transmission channels, we show that terrorism does not have distributional consequence by damaging the economy. Rather, in democracies terrorism leads to lower levels of redistribution via taxation and transfers. This finding is consistent with our theoretical argument that terrorism elicits a policy response in the form of lower levels of redistribution especially from democratic governments due to their dependence on broad electoral support to stay in power.
Keywords: D31; D74; 330; Terrorism; Income inequality; Wealth inequality; Democracy